APLIKASI BERBAGAI AUKSIN UNTUK MEMACU PERTUMBUHAN VEGETATIF ANGGREK DENDROBIUM PASCA AKLIMATISASI - Asih, Asih; Astutik, Astutik; Sumiati, Astri (Universitas Tribhuwana Tunggadewi, 2019)
Dendrobium is one of the most popular types of ornamental plants in the community. The study aims to determine the type of auxin hormones and the right concentration to stimulate the vegetative growth of Dendrobium. The study was conducted at Jalan Tlogomas green house, Lowokwaru Subdistrict, Malang. Research for 3 months (February-May 2018). Research using a completely randomized design (CRD) factorial 2 factors, namely: Factor I is the type of Auxin (H), namely: H1 = hormones NAA (Naphthalene Acetic Acid) H2 = hormones IAA (Indoleacetic Acid) and H3 = hormones IBA (Indolebutynic Acid) Factors II is Concentration (K), namely: K0 = 0 ppm (control) K1 = 50 ppm (mg / l) K2 = 100 ppm (mg / l) and K3 = 150 ppm (mg / l). Parameters of observation include growing new shoots, increasing the number of leaves, increasing the length of the leaves, increasing the width of the leaves and the percentage of life%. The results showed that there were interactions between types of auxin and concentration on the number of leaves (aged 6-12 weeks). Hormones that are more suitable to stimulate Dendrobium growth are IBA 100 ppm with an increase in the number of leaves by 1.78. IBA hormone is more suitable to stimulate Dendrobium growth characterized by the fastest growth of shoots, increase in leaf length (1.18 cm) and optimal auxin concentration is between 50-100 ppm. Dendrobium merupakan salah satu jenis tanaman hias yang paling banyak diminati oleh masyarakat. Penelitian bertujuan untuk mengetahui jenis hormon auksin dan konsentrasi yang tepat untuk memacu pertumbuhan vegetatif Dendrobium. Penelitian dilaksanakan di green house Jalan Tlogomas Kecamatan Lowokwaru, Malang. Penelitian selama 3 bulan (Februari-Mei 2018). Penelitian menggunakan Rancangan Acak Lengkap (RAL) faktorial 2 faktor yaitu: Faktor I adalah jenis Auksin (H) yaitu: H1= hormon NAA (Naphthalene Acetic Acid) H2 = hormon IAA (Indoleacetic Acid) dan H3 = hormon IBA (Indolebutynic Acid) Faktor II adalah Konsentrasi (K) yaitu: K0 = 0 ppm (kontrol) K1 = 50 ppm (mg/l) K2 = 100 ppm (mg/l) dan K3 = 150 ppm (mg/l). Parameter pengamatan meliputi saat tumbuh tunas baru, pertambahan jumlah daun, pertambahan panjang daun, pertambahan lebar daun dan presentase hidup %. Hasil penelitian menunjukan terdapat interaksi antar jenis auksin dan konsentrasi terhadap pertambahan jumlah daun (umur 6 - 12 minggu). Hormon yang lebih sesuai untuk memacu pertumbuhan Dendrobium adalah IBA 100 ppm dengan pertambahan jumlah daun sebesar 1,78. Hormon IBA lebih sesuai untuk memacu pertumbuhan Dendrobium ditandai dengan saat tumbuh tunas paling cepat, pertambahan panjang daun (1,18 cm) dan konsentrasi auksin yang optimal adalah antara 50-100 ppm.